ANALISIS REAKSI PASAR BURSA EFEK INDONESIA SEBELUM DAN SESUDAH PENGUMUMAN RIGHT ISSUE TERHADAP ABNORMAL RETURN DAN LIKUIDITAS SAHAM (Studi Kasus Pada Perusahaan-Perusahan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2015-2018 Sektor Infrastruktur) - Yehofa Wajin (RJABM (Research Journal of Accounting and Business Management), 2019)
Go public companies in order to increase funds, companies can conduct corporate actions, namely rights issues. Right issue is a new share offering from the company for old investors with a system offering it to an old investor first. The information about the rights issue was published as an announcement that could be used to see market reactions. This market reaction is measured by abnormal returns to see stock returns and trading volume activity to see stock liquidity.This research intend to see abnormal stock returns and stock liquidity before and after the announcement of the rights issue with a sample of infrastructure sector companies in the Indonesia Stock Exchange for the period 2015-2018 with purposive sampling technique of sample selection, according to predetermined criteria then obtained 6 companies.This research is a descriptive study using quantitative methods. The test used in this study is the normality test then using a paired sample t-test. The results of this study show no significant difference from abnormal returns and stock liquidity before and after the announcement of the rights issue.